Consumer benefits received in the Instagram account on brand trust and commitment - Gancar Candra Premananto, Muhammad Ansyarulah Syuhada, (Opción, 2020)
This study aims to determine the effect of consumer benefits on active participation that has implications for brand trust and brand commitment. This study used a quantitative approach using SEM analysis with SmartPLS 3.0 program and primary data of 146 respondents who were followers of Instagram account @starbucksindonesia. The results showed that two types of consumer benefits affected the level of active participation followers namely social-psychological benefits (2,914> 1.65) and hedonic benefits (4,997> 1.65). In conclusion, some consumer benefits were able to influence active participation which has implications for brand trust and brand commitment.